Dusty casson fluid flow containing single-wall carbon nanotubes with aligned magnetic field effect over a stretching sheet - Nur Syamilah, Arifin; Abdul Rahman, Mohd Kasim; Syazwani, Mohd Zokri; Siti Farah, Haryatie; Mohd Zuki, Salleh (Penerbit Akademia Baru, 2023)
Two-phase flow is the mutual interaction between solid and fluid phases which encountered in real life applications, such as sedimentation, blood flow, water pollution, fluidized bed and to name a few. In the theoretical study, this binary mixture is represented by partial differential equations that denotes its physical properties of all phases. Therefore, the interaction between three important elements over a stretching sheet is examined in this study where the focus is on Casson fluid, single-wall carbon nanotubes (SWCNTs) and dust particles. Moreover, the aligned magnetic field effect and Newtonian heating (NH) are associate together to influence the flow region. In order to generate the results, the equations that governed the current model must therefore employ the similarity variables to produce the ordinary differential equations. Formulation of the problem is then continued by solving the resulting equations using Runge-Kutta Fehlberg (RKF45) method. Significant outputs for considered parameters are presented through graph. It is found that, the growing effect of fluid-particle interaction particle decreases the fluid phase distribution which contributes to the opposite trend in dust phase.